POLA PEMBERIAN AIR SUSU IBU (ASI) DAN STATUS GIZI IBU MENYUSUI DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU, KOTA SEMARANG - Wardatus Zahro; Dina Rahayuning Pangestuti; Laksmi Widajanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Breastfeeding mothers are the ones who belong to the vulnerable group of nutrition, because breast milk (ASI) which is the main food for infant obtained from the mothers. Research conducted in 2009 showed 34,6% of nursing mothers in Indonesia at risk of chronic energy deficiency (CED), especially predominant breastfeeding mothers. This research was conducted in Puskesmas Kedungmundu which aims to determine the relationship between breastfeeding pattern and maternal nutritional status. This type of research is an analytic observational with cross sectional approach. Samples were divided into two groups: non-exclusive breastfeeding and exclusive breastfeeding and obtained by purposive sampling number of 34 mothers. Data were collected through interviews and measurements of nutritional status using anthropometry methods then analyzed using univariate and bivariate analysis. Bivariate analysis using Chi Square and Rank Spearman correlation. BMI, MUAC, and percent body fat measurement results shows that there are 20,6% mothers were overweight in non-exclusive breastfeeding mothers, 17,6% mothers at risk of CED in non-exclusive breastfeeding mothers and 23,5% mothers experiencing over fat and obese on non-exclusive breastfeeding mothers. Statistical analysis showed there is no correlation between breastfeeding pattern with maternal BMI (p=0,132), there was no correlation between breastfeeding pattern with maternal MUAC (p=0,452) and there is no correlation between breastfeeding pattern with maternal percent body fat (p=0,730). Suggestions from this research are health centers are expected to reduce the nutritional problems in nursing mothers through increased coverage of exclusive breastfeeding, because exclusive breastfeeding is more effective maintaining maternal nutritional status in normal conditions.